Responses of Seagrass Amphibolis antarctica Roots to Nutrient Additions Along a Salinity Gradient in Shark Bay, Western Australia - Husen Rifai; Firman Zulpikar; Muhammad Safaat; Jeverson Renyaan; Laode Alifatri; Asep Rasyidin (Journal Omni-Akuatika, 2021)
Seagrass meadows in oligotrophic environments are particularly susceptible to nutrient enrichment, yet morphological and architectural seagrass root responses in these ecosystems are poorly understood. This study aimed to investigate the response of Amphibolis antarctica, one of dominant seagrass species in Shark Bay, roots to nutrient additions along a salinity gradient in the oligotrophic ecosystem of Shark Bay, Western Australia. A fully factorial nutrient additional experiment with four treatments (Control, N, P and N+P) was conducted at each of five sites along a salinity gradient (between ~38ppt in site 1 and ~50ppt in site 5) in Shark Bay across a three-year period (2012-2015). In the laboratory, the roots morphology and architecture A. antarctica were investigated using a software (WinRhizo). Then, a two-way analysis of variance (ANOVA) was performed to investigate if there was a significant change in the morphology and architecture of the roots after the nutrient inputs and along five sites with salinity gradient. There was no significant impact of nutrient addition on the root’s morphology and architecture of A. antarctica species. However, the effect of site factor with salinity gradient was significant to all morphological aspects (total root length, root surface area and root diameter) of A. antarctica roots. These findings highlight the more ecological function of A. antarctica roots being in anchoring of the plant into the seafloor rather than to absorb nutrient from the sediment.Keywords: Nutrient addition, Oligotrophic habitats, Amphibolis antarctica, Shark Bay